The Limits and Possibilities of the ASEAN Way: The Case of Rohingya as Humanitarian Issue in Southeast Asia - Tobing, D H (KnE Social Sciences, 2018)
The ASEAN Way has been considered by many academics as the most problematic, yet superior principles in ASEAN decision and policy-making process. The principles highly emphasize on traditional concept sovereignty of its member states, which leads to the perception of ASEAN’s inability to reconcile the ASEAN Way and humanitarianism. In this research, despite the two competing perspectives of whether the ASEAN Way is hindering or enhancing the ability of ASEAN to settle conflicts, this research argues that the extent to which the ASEAN Way becomes limitation or accelerator depends on the nature of the conflict. Not to deny that the ASEAN Way may be the only possible mechanism to approach Myanmar, but the ASEAN Way itself is not enough because there is a tendency for ASEAN members turning ‘a blind eye’ towards a conflict that does not reach into the surface or there is no proper discussion about it. To support the argument, this research will illustrate the above-mentioned argument through the recent case of massive Rohingya human rights prosecution that results in the biggest crisis in sea after Indo-China. This research will do so by; first, exploring the nature of the ASEAN way and second, applying the conceptual discussion to the case of Rohingya in order to show the limits of the ASEAN way in this particular case. Keywords: ASEAN, ASEAN Way, Humanitarian, Refugee, Rohingya, Southeast Asia